IMPLEMENTATION OF MOBILE-BASED APPLICATIONS USING PROTOTYPES FOR WASTE AND WATER MANAGEMENT - Joko Dwi Mulyanto; Saifudin Saifudin; Supriatiningsih Supriatiningsih; Corie Mei Hellyana; Eva Argarini Pratama (Jurnal Scientia, 2023)
Waste is a problem faced by almost all countries worldwide. There are several operational technical problems in waste management, such as adequate sorting, containerization, collection and transportation systems. The waste disposal and collection process does not separate organic, inorganic and B3 waste. Apart from that, the route for transporting waste from the rubbish bin to the final disposal site takes quite a long time. Therefore, a mobile-based system that aims to overcome this problem is needed. So you can find out the characteristics of waste in the form of the amount and type of waste produced and provide a design for an effective and efficient waste sorting, container, collection and transportation system. In this way, it can improve the current waste management process. The implementation of this system uses the prototype method with the help of Unified Modeling Language tools for depicting system flow diagrams such as use case, activity, Entity Relationship Diagram, Logical Record Structure, class and sequence diagrams which sequentially form a unified system making prototypes or designing mobile apps using Figma. By using computerized mobile app design, it can provide an overview of the waste management system for BUMDes.